Analisis Sistem Antrian Kendaraan Bermotor Menggunakan Metode Discrete-Event Simulation pada SPBU 14.2031143 Tanjung Anom Deli Serdang - Sarah, Siti; Muthmainnah H, Nazwa Aliya; Suffi P, Aisyah Fadilla; Amri, M Choirul (MEANS (Media Informasi Analisa dan Sistem), 2025)
This study aims to analyze the performance of the motor vehicle queuing system at gas station 14.2031143 Tanjung Anom Deli Serdang using the Discrete-Event Simulation (DES) approach. Data was obtained through direct observation for 1 hour and 10 minutes by recording the arrival time, start of service time, and end of service time for each vehicle. The results of data processing show that the average waiting time for vehicles reached 5 minutes and 42 seconds, which is much higher than the average service time of 25 seconds. This condition indicates that the main problem lies in the density of the queue lane, not in the service process. Based on these results, a DES simulation model was developed to represent the actual behavior of the queueing system and used as the basis for evaluating improvement scenarios. The main scenario tested was the addition of parallel queuing lanes to reduce vehicle congestion in a single line. The simulation results showed that the addition of lanes significantly reduced waiting times and improved the smooth flow of the queue without requiring changes to service facilities. This study concludes that adding queue lanes is an effective and feasible solution to improve the efficiency of the queue system at gas stations, and can be implemented as a measure to improve service during busy operating hours.